KONSEP EKONOMI DAN PERBANDINGANNYA ANTARA KAPITALIS, SOSIALIS DAN ISLAM - Muhamad Husaini; Nurul Ahilatun Nadifah (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2023)
The world economy has so far been basically dominated by the capitalist economic system and the social economy, both of which have had a tremendous impact on the people's economy and this impact has been felt on social problems. The research aims to find out knowledge about capitalist and Islamic economics as well as their comparisons. This research is descriptive qualitative with data sources from various literature studies, social media article books. The results of this study are: (1) The capitalist economic system, characterized by economic organization of private or individual property rights, the socialist economic system, prioritizes togetherness as well as the role of the government is very strong. meaning that all decisions related to goods and services to be produced are decided by the government and the Islamic economic system are economic issues in the people that are inspired by Islamic values. (2) The comparison between the capitalist, socialist and Islamic economic systems is that the Islamic economic system has the advantages that exist in the capitalist and socialist economic systems, but is free from the weaknesses found in both systems